Presacral schwannoma: a bizarre presentation in the Pandora’s box of abdomen and pelvis - Poojary, Harsha S.; Sherigar, Vishwanath; Balaji, Abhinav (International Surgery Journal, 2020)
Schwannomas are benign tumors arising from the Schwann cells of nerve fibers. They are extremely rare in the pelvis accounting for only 1-3% of all schwannomas. These tumors are nonaggressive, slow growing, solitary neoplasms with an extremely low possibility of malignant transformation or recurrence after excision. We present a case of a 19 years old male with complaints of radiating pain from lower back to the left thigh associated with altered bowel and bladder habits. Following a detailed work up he underwent laparotomy and mass excision. Histopathological report revealed presacral schwannoma. Post-surgery patient improved symptomatically and is on regular follow up. There are a smaller number of cases of presacral schwannoma reported in the literature. Due to its outlandish striking presentation, diagnosis is very challenging. Although presacral schwannoma is rare, it should be considered as a differential diagnosis in the back of the mind of a surgeon while dealing a case of pelvic mass. In symptomatic and asymptomatic cases, surgical excision is the mainstay of treatment of these tumors.